Influence of alloying elements and heat treatment on the mechanical properties of chromium cast iron - E. I. Marukovich; V. M. Ilyushenko; V. A. Pumpur; V. M. Andrienko; P. Yu Duvalov (Литьë и металлургия, 2020)
The results of experimental studies to determine the effect of alloying and heat treatment on the mechanical properties of the high-chromium cast iron are described. When alloying the melt with nickel, molybdenum and manganese, as well as during heat treatment by quenching, specific wear, tensile strength in bending of the obtained samples, their hardness and microhardness were studied. A comparative analysis of the influence of alloying elements and heat treatment methods has been performed. When alloying Ni, Mo, and Mn, cast specimens that have not undergone heat treatment have the highest specific wear. It was established that the hardened Ni alloyed samples have the greatest bending strength. It was found that cast samples that were not subjected to heat treatment have much lower hardness and microhardness. The approximate composition of chromium cast iron was determined for further studies to increase its wear resistance. The research results are used in the manufacturing process of parts for crushing and grinding equipment.